Irisin: A potentially candidate marker for myocardial infarction - Kuloglu, Tuncay; Aydin, Suna; Eren, Mehmet Nesimi; Yilmaz, Musa; Sahin, Ibrahim; Kalayci, Mehmet; Aydin, Suleyman (Elsevier Science Inc, 2014)
Myocardial infarction (MI) causes energy depletion through imbalance between coronary blood supply and myocardial demand. Irisin produced by the heart reduces ATP production by increasing heat generation. Energy depletion affects irisin concentration in circulation and cardiac tissues, suggesting an association with MI. We examined: (1) irisin expression immunohistochemically in rat heart, skeletal muscle, kidney and liver in isoproterenol (ISO)-induced MI, and (2) serum irisin concentration by ELISA. Rats were randomly allocated into 6 groups (n=6), (i) control, (ii) ISO (1 h), (iii) ISO (2 h), (iv) ISO (4 h), (v) ISO (6 h), and (vi) ISO (24 h), 200 mg ISO in each case. Rats were decapitated and the blood and tissues collected for irisin analysis. Blood was centrifuged at 1792 g for 5 min. Tissues were washed with saline and fixed in 10% formalin for histology. Serum irisin levels gradually decreased from 1 h to 24h in MI rats compared with controls, the minimum being at 2 h, increasing again after 6 h. Cardiac muscle cells, glomerular, peritubular renal cortical interstitial cells, hepatocytes and liver sinusoidal cells and perimysium, endomysium and nucleoi of skeletal muscle were irisin positive, but its synthesis decreased 1-4 h after MI. At all time-points, irisin increased near myocardial connective tissue, with production in skeletal muscle, liver and kidney recovering after 6 h, although slower than controls. Unique insight into the pathogenesis of MI is shown, and the gradually decrease of serum irisin might be a diagnostic marker for MI. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Irisin; Myocardial infarction; Isoproterenol; Heart; Skeletal muscle; Kidneys